Pemberian Ekstrak Buah Pare dan Diet Tinggi Lemak pada Penurunan Berat Badan Tikus Putih Jantan - I MADE SUBHAWA HARSA (Universitas Hang Tuah, 2019)
Abstract Background : Obesity is an energy balance disorder, ketogenic diet can reduce body weight. Bitter melon (Momordica charantia L.) is a type of vegetable material that is often used as an antioxidant, hypocholesterolemia and hypotriglyceridemia drug. Cucurbitasin is a substance produced by bitter melon (Momordica charantia L.) with a bitter taste which causes in decreasing appetite, resulting in a decrease in triglycerides. This is caused by the bioactivity of bitter melon (Momordica charantia L.) which can increase lipid oxidation, which causes the accumulation of decreased fat tissue which can reduce weight. Methods: This research using pre and post test randomized controlled group design with sample size of 30 male white rats (Rattus norvegicus) wistar lines divided into 3 groups, group 1 as negative control group given standard feed, group 2 as positive control group given high-fat diet with a dose of 2.5 ml and group 3 as a treatment group given a high-fat feed with dose of 2.5 ml and extract of bitter melon (Momordica charantia L.) at dose of 37.5 mg / 150 gBB by feeding tube every morning for 28 days. Data were analyzed by T-paired tests. Result: The T-paired test in each group found a significantly different result of p = 0,000. Conclusion: given bitter melon (Momordica charantia L.) extract and high-fat diet can reduce weight in male white rats (Rattus norvegicus). Keywords:Bitter molon extract, high fat feed, weight loss